2022
DOI: 10.1002/chem.202203505
|View full text |Cite
|
Sign up to set email alerts
|

Boron‐Mediated Regioselective Aromatic C−H Functionalization via an Aryl BF2Complex

Abstract: An efficient regioselective functionalization of 2aryl-heteroarenes and aryl aldehydes via an azaaryl BF 2 complex has been developed. Mechanistically the reaction comprises fluoride to bromide ligand exchange on an aryl boron species and consecutive CÀ B bond cleavage to deliver a broad range of functionalized products. The reaction is high yielding, has a broad substrate scope where several different heteroarenes can be functionalized with chloro, bromo, iodo, hydroxyl, amine and BF 2 in a highly regioselect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…On the basis of the results described above and previous reports, , a mechanism is proposed for this metal-free C–H borylation reaction (Scheme ). Initially, the coordination of 1a to BBr 3 formed Lewis acid–base adduct A , which further produced borenium cation B via the transfer of a bromide anion to another BBr 3 .…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…On the basis of the results described above and previous reports, , a mechanism is proposed for this metal-free C–H borylation reaction (Scheme ). Initially, the coordination of 1a to BBr 3 formed Lewis acid–base adduct A , which further produced borenium cation B via the transfer of a bromide anion to another BBr 3 .…”
mentioning
confidence: 70%
“…Impressively, in 2019, the groups of Shi and Houk and Ingleson simultaneously reported the metal-free acyl-directed electrophilic C–H borylation of anilines and indoles with BBr 3 accessing the ortho -borylated anilines and C4/C7-borylated indoles. Since then, a variety of acyl-, nitrogen-, and phosphine-directed metal-free ortho -selective aromatic C–H borylations using BBr 3 have been successively developed using a similar strategy . Inspired by these reports, we envisioned that the ortho C–H borylation of thiobenzamides might be achieved via a S-directed electrophilic borylation approach, although it has seldom been explored .…”
mentioning
confidence: 99%
“…2-Bromobenzaldehyde (4h). 24 The crude mixture was purified by column chromatography on a silica gel (hexane/EtOAc as an eluent), and product 4h (22.6 mg, 61% yield) was obtained as a colorless liquid. 1 H NMR (500 MHz, CDCl 3 ) δ 10.34 (s, 1H), 7.92−7.86 (m, 1H), 7.65−7.61 (m, 1H), 7.45−7.39 (m, 2H); 13 C{ 1 H} NMR (126 MHz, CDCl 3 ) δ 191.9, 135.4, 134.0, 133.6, 130.0, 128.0, 127.2.…”
Section: -Bromobenzaldehyde (4g) 5cmentioning
confidence: 99%
“…[7] More recently, we showed that the chemistry is not limited to only hydroxyl and Bpin, but it can also be used for installing halogens to phenyl pyridines and aryl aldehydes (Figure 1C). [8] Figure 2. This work: Boron-directed regiospecific halodeboronation of N-aryl amides and ureas.…”
Section: Introductionmentioning
confidence: 99%